Violence and democracy - Keane, John (Contemporary political theory, 2004)
In this provocative book, first published in 2004, John Keane calls for a fresh understanding of the vexed relationship between democracy and violence. Taking issue with the common sense view that 'human nature' is violent, Keane shows why mature democracies do not wage war upon each other, and why they are unusually sensitive to violence. He argues that we need to think more discriminatingly about the origins of violence, its consequences, its uses and remedies. He probes the disputed meanings of the term violence, and asks why violence is the greatest enemy of democracy, and why today's global 'triangle of violence' is tempting politicians to invoke undemocratic emergency powers. Throughout, Keane gives prominence to ethical questions, such as the circumstances in which violence can be justified, and argues that violent behaviour and means of violence can and should be 'democratised' - made publicly accountable to others, so encouraging efforts to erase surplus violence from the world